Usaha Hamba Tuhan Memaksimalan Penggunaan Teknologi Sebagai Wujud Penerapan Misio Dei Bagi Dunia Di Era Digital - Freddy Lans Deo Dawolo (Publisher STPKat, 2023)
In human history, changes have always occurred, so everyone must be able to keep up with changes in order to adapt. For example, in terms of technological progress, the changes are increasingly unstoppable. In general, the most popular digital technology today is social media. The purpose of writing this article is to discuss how God's people can utilize technology in an effort to maximize the application of divine mission (Misio Dei) for the world in the digital era. With this, the research method used by the author is a qualitative research method. For this reason, the Servant of God needs to utilize social media as a tool to spread the gospel message and promote it. They need to have an effective strategy for using social media, such as creating interesting and relevant content, interacting with congregations online, and utilizing social media features to spread church messages. Servants of God need to keep abreast of technological developments and adopt the latest technologies that are relevant to the mission of the church. Because, this article aims to provide guidance and inspiration to God's people on how to use technology effectively and responsibly in the context of ecclesiastical missions.